Care for the Acquired Immunodeficiency Syndrome in the contemporary world: understanding practitioners’ view - Suto, Cleuma Sueli Santos; Paiva, Mirian Santos; Oliveira, Jeane Freitas de; Rodrigues, Andreia Silva; Oliveira, Daiane Santos; Porcino, Carlos Alberto (Rev Rene, 2018)
Objective: to understand the perspective of health professionals on care for people with acquired immunodeficiency syndrome. Methods: this is a qualitative approach based on the Social Representation Theory based on the free speeches of 73 practitioners from four specialized public services, which were submitted to Factorial Correspondence Analysis. Results: practitioners with longer training and working time have emphasized aspects related to the syndrome such as physical degradation, abandonment and death; practitioners with shorter training and working time have represented the care of the person living with human immunodeficiency virus as an increased knowledge of sensitivity, indicating attitudes and behaviors socially constructed and accepted as belonging to health practitioners. Conclusion:practitioners with more experience have seen the syndrome in its negative and initial aspect; the newcomers to the professional practice have shown sensitivity and openness to the relevant issues of this phenomenon and concrete possibilities of more effective/transforming care practices.